Želimir Žilnik and Eastern European independent cinema - Mazierska, Ewa (Wydawnictwo Naukowe UAM w Poznaniu; Wydawnictwo PWSFTViT w Łodzi, 2013)
In my paper I will discuss the career of, a director born in 1942 in Nis in Yugoslavia, whose career, spanning over forty years and Yugoslavia, West Germany and Serbia, excellently illustrates the concepts of independent and transnational cinema and their interface. Žilnik’s career well illustrates the advantages and pitfalls of “independent filmmaking”, especially in the context of Eastern Europe. Hence, in my paper, I will use his case to examine this concept, drawing on Marx and Marxist thought, such as the critique of the “culture industry” by Horkheimer and Adorno and the concept of “critical media” by Christian Fuchs, and the history of Eastern Europe and its cinema, with its figure of “artist-dissident” and the specific case of Yugoslavia. My main point is that there is no “independent cinema” in absolute terms; cinema can only be independent from something, hence ‘independent cinema’ means different things in different cultural contexts.
Keywords: Independent cinema; transnational cinema; Eastern Eurpean cinema; critical media; cultural industries; Marxism